(untitled) (Medico Legal Update, 2020)
Objective: Nausea and vomiting (NVP) are among the most common symptoms during pregnancy. NVP causes emotional and psychological distress and can have a profound impact on a woman’s quality of life (QoL). Material and Method: Vitamin D3 and Vitamin B6,se and electrolytes (Mg+2,K+) levels were determined in first and second trimesters in 120 women suffering from nausea and vomiting of pregnancy,30 pregnant women free of symptoms, age identical between the ages of (17-45) years. Results: Vitamin D3 Vitamin B6, K+, Se and Mg+2 in the blood showed a significant decrease in all patients as compared to control group (P ? 0.05). Conclusion: In patients with NVP and NP we find a significant reduction in level of Vit.D3, and decrease in level of serum Vit. B6,K+, Se and Mg+2. In first trimester found a decrease in levels of Vit.D3, Vit.B6 and K+ more from second trimester,while in first trimester found an increase in levels Se, Mg+2 more from second trimester.